Exploring the impact of encapsulation on the stability and bioactivity of peptides extracted from botanical sources: trends and opportunities - Pérez-Pérez, Viridiana; Jiménez-Martínez, Cristian; González-Escobar, Jorge Luis; Corzo-Ríos, Luis Jorge (Frontiers in Chemistry, 2024)
Bioactive peptides derived from plant sources have gained significant attention for their potential use in preventing and treating chronic degenerative diseases. However, the efficacy of these peptides depends on their bioaccessibility, bioavailability, and stability. Encapsulation is a promising strategy for improving the therapeutic use of these compounds. It enhances their stability, prolongs their shelf life, protects them from degradation during digestion, and enables better release control by improving their bioaccessibility and bioavailability. This review aims to analyze the impact of various factors related to peptide encapsulation on their stability and release to enhance their biological activity. To achieve this, it is necessary to determine the composition and physicochemical properties of the capsule, which are influenced by the wall materials, encapsulation technique, and operating conditions. Furthermore, for peptide encapsulation, their charge, size, and hydrophobicity must be considered. Recent research has focused on the advancement of novel encapsulation methodologies that permit the formation of uniform capsules in terms of size and shape. In addition, it explores novel wall materials, including polysaccharides derived from unconventional sources, that allow the precise regulation of the rate at which peptides are released into the intestine.